Zygomatico-orbital intra-arterial melphalan infusion for intraocular retinoblastoma. (11th July 2011) - Cooke, Daniel; Farid, Hamed; Kim, Warren; Dowd, Christopher; Higashida, Randall; Halbach, Van
Abstract : Retinoblastoma is a rare and curable malignancy affecting the pediatric population. For advanced stage intraocular retinoblastoma, enucleation remains the primary treatment modality, although the use of laser photocoagulation, cryotherapy, radiotherapy and chemotherapy are frequently used, particularly in the setting of bilateral disease. Intravenous chemotherapy is the long-standing method of delivery, but local administration (subtenon, intravitreal or intra-arterial) is gaining in popularity because of the reduced side effects related to systemic administration. Of these newer methods, intra-arterial infusion has demonstrated technical feasibility, few procedural complications and robust tumor response. A case is described where a collateral supply to the affected ophthalmic artery was via the zygomatico-orbital branch of the ipsilateral superficial temporal artery. Melphalan infusion was performed via this pathway without incident.